Pre-emergence herbicidal efficiency and uptake of atrazine-loaded zein nanoparticles: a sustainable alternative to weed control - Carvalho, Lucas Bragança [UNESP]; Godoy, Isabela Silva; Preisler, Ana Cristina; de Freitas Proença, Patrícia Luiza [UNESP]; Saraiva-Santos, Telma; Verri, Waldiceu Aparecido; Oliveira, Halley Caixeta; Dalazen, Giliardi; Fraceto, Leonardo Fernandes [UNESP] (Royal Society of Chemistry (RSC), 2023)
In this study, we describe the development of zein nanoparticles associated with the herbicide atrazine and evaluate the pre-emergence activity of this formulation against a target (Brassica juncea) and a non-target (Zea mays) plant, as well as its soil mobility and uptake/transport in the tissues of Bidens pilosa plants. The proposed nanoformulation showed good colloidal stability, with nanoparticles of spherical shape, sizes between 130 and 170 nm, and an encapsulation efficiency of the active ingredient above 90%. The nanoencapsulation provided greater herbicide effectiveness against B. juncea, even at a dose 80 times lower than the recommended, without posing toxicity to the crop species. The monitoring of FITC-labeled nanoparticles indicated that the nanostructures were captured and accumulated in B. pilosa and Z. mays roots, but were poorly transported to the shoot. In addition, atrazine nanoencapsulation did not increase the mobility of the herbicide in the soil compared to the conventional formulation, remaining at the upper soil fractions, where the seed bank is located. Thus, these findings highlight the potential of this nanoformulation as an alternative for weed control.